Immigration and Electoral Support for the Far Left and the Far Right - Anthony Edo; Yvonne Giesing; Jonathan Öztunc; Panu Poutvaara (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2017)
Immigration has become one of the most divisive political issues in the United States, the United Kingdom, France and several other Western countries. We estimate the impact of immigration on voting for far-left and far-right parties in France, using panel data on presidential elections from 1988 to 2012. To derive causal estimates, we instrument more recent immigration flows by past settlement patterns in 1968. We find that immigration increases support for far-right candidates and has no robust effect on far-left voting. The increased support for far-right candidates is driven by low-skilled immigrants from non-Western countries.
Keywords: D72; F22; J15; P16; 330; Voting; immigration; political economy